„Religion und Königtum sind Zwillinge“ –: Herrschaft und Religion in den römisch-sasanidischen Beziehungen des 3. und 4. Jahrhunderts n. Chr. - Beigel, Thorsten (Comparativ, 2008)
In the 4th century, both in the Roman and in the Sasanian empire religion and politics were combined in new ways. Christianity gradually rose to the position of the official religion in Rome, while Zoroastrianism was institutionalized as an official cult in Persia. Institutional changes introduced by the Sasanians can be interpreted partly as a reaction to Roman models and policies, and changing attitudes of the Sasanian emperors to their Christian subjects, as well as to Jews and Manichaeans, should be seen as a reflection of shifting Roman policies towards „orthodox“ and „heretical“ Christians.